When Names Speak: A Sociolinguistic Analysis of Street Toponymy in Kupang City, East Nusa Tenggara-Indonesia - Nenotek, Seprianus A (English Education Study Program - Artha Wacana Christian University, 2025)
Street toponymy represents a form of naming that encapsulates social, political, and cultural memory within public spaces. In Kupang City, street names function not only as locational markers but also as symbols of collective identity, historical traces, and representations of power. This study aims to uncover the social, historical, and ideological meanings embedded in the street names of Kupang City through a sociolinguistic approach. The research employs a qualitative-descriptive method, with data collected through documentation and interviews. The findings indicate that street naming practices in Kupang reflect social power dynamics, honor significant historical figures, and symbolize local cultural values. The street names fall into various categories, including National and Local Figures, Historical Events, Local or Ethnic Names, Natural and Geographical Features, and Religious References. This article argues that street names serve as spatial narratives that “speak” about who is honored, what values are commemorated, and which collective memories are preserved in urban society. The study contributes significantly to the toponymic scholarship in Eastern Indonesia, particularly in Kupang City. It strengthens the critical sociolinguistic perspective by highlighting street naming as a representation of power, identity, and collective memory, while also promoting interdisciplinary inquiry and a deeper understanding of public space as a symbolic socio-cultural domain.